2023
DOI: 10.1111/epi.17550
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as advanced second‐line treatment in benzodiazepine‐refractory convulsive status epilepticus in children

Abstract: Status epilepticus (SE) is one of the most common neurological emergencies in children. To date, there is no definitive evidence to guide treatment of SE refractory to benzodiazepines. The main objectives of treatment protocols are to expedite therapeutic decisions and to use fast-and short-acting medications without significant adverse effects. Protocols differ among institutions, and most frequently valproate, phenytoin, and levetiracetam are used as second-line treatment. After failure of first-and second-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…In the operant test battery, ketamine‐exposed animals performed significantly worse than controls in learning, color and position discriminations, accuracy, and speed of task performance. This is highly relevant for seizure management, as ketamine is increasingly being used in the treatment of refractory seizures and status epilepticus 42 . The present results in the PbM‐treated animals conform with those of Paule et al and strongly argue that treatment duration is critical for neurocognitive outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the operant test battery, ketamine‐exposed animals performed significantly worse than controls in learning, color and position discriminations, accuracy, and speed of task performance. This is highly relevant for seizure management, as ketamine is increasingly being used in the treatment of refractory seizures and status epilepticus 42 . The present results in the PbM‐treated animals conform with those of Paule et al and strongly argue that treatment duration is critical for neurocognitive outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…This is highly relevant for seizure management, as ketamine is increasingly being used in the treatment of refractory seizures and status epilepticus. 42 The present results in the PbM-treated animals conform with those of Paule et al and strongly argue that treatment duration is critical for neurocognitive outcomes. Notably, we have reported that 5-hour sevoflurane or 8-hour PbM treatment cause significantly less brain injury than 24 hours of PbM treatment.…”
Section: And Alone Condition [A2]supporting
confidence: 91%
“…In this regard, various studies have shown that ketamine has anticonvulsant and neuroprotective characteristics [ 21 ]. Recent research has demonstrated that ketamine can be utilized to effectively control refractory status epilepticus [ 22 ]. McCarthy et al 23 published the first evidence that ketamine exerts an anticonvulsant effect in animal models in 1965.…”
Section: Discussionmentioning
confidence: 99%
“…The second study 10 adds important data in neonates and younger children to the world literature to suggest that ketamine, a noncompetitive N-methyl-D-aspartate receptor antagonist, can be effectively and safely used to treat adults and children with RSE as the first CIV ASM. 1,2 Unfortunately, long-term patient outcomes were not reported in either study.…”
Section: Commentarymentioning
confidence: 97%
“…1 To reduce complications from RSE, clinicians often select a continuous intravenous anesthetizing ASM (CIV ASM) as the third drug. 2 Continuous intravenous anesthetizing ASMs in current use are midazolam, pentobarbital, and propofol, but there have been several newer reports on the use of ketamine. The desire to quickly stop RSE is understandable, but there are 2 questions to consider when considering a CIV ASM.…”
Section: Commentarymentioning
confidence: 99%